BIODETERIORATION OF CELLULOSE MATERIALS IN KARINGOTE, NILESWARAM, KAVVAYI AND RAMAPURAM BACKWATER SYSTEMS OF KERALA - NAIR, N. BALAKRISHNAN (Journal of Indian Fisheries Association, 2015)
The hydrographic conditions prevailing in an estuarine system along the southwest coastof India are described. The nature of destruction of timber in these backwaterÂ·s has beenexamined in detail which revealed the existence of 8 species of shipworms, 2 species each ofJlholads and isopods. The shipworms arc represented by Dicyathifer mmmi, Lyroduspedicellatus, Teredo furcifera, Teredo clappi, Nausitora dunlopei, Bankia carinata, Bankiacampanellata; the J>holads by Martesia striata and Martesia (Particoma) nairi; and the isopodsby Sphaeroma terehrans and Sphaeroma annamlalei. The incidence and relative abundanceof these pests arc discussed in relation to the salinity profile of the estuary.